REYOG OBYOGAN IN PHOTO ESSAY - Nugroho, Oki Cahyo; Tricana, Deny Wahyu (Seni Media Rekam ISI Surakarta, 2019)
Reyog is one of the traditional arts that shows a richness of Indonesian culture. This art is unique and interesting to be realized in the form of visual works and meaningful, especially the art of photography. Photography has an important role as a medium for delivering information in the form of images, moreover images are a universal language. This research uses the method of creation with stages, namely observation, exploration, selection, and correction as well as analysis and presentation of data in order to uncover the phenomena that occur in Reyog Ponorogo. The results of this study indicate that 1) the shooting of an essay about performance of reyog obyogan Ponorogo's typical requires adequate photographic technical mastery; 2) the use of digital processing can support the visualization of photos essays of reyog obyogan; and 3) the mastery of technical shooting and digital processing is able to portray the characteristics of the reyog obyogan that are distinctive and full of traditional aesthetic values.